1982
DOI: 10.1139/b82-068
|View full text |Cite
|
Sign up to set email alerts
|

Birdsfoot trefoil (Lotus corniculatus) root nodules: morphogenesis and the effect of forage harvest on structure and function

Abstract: Nodule structure, nodule enzymes of ammonia assimilation, nitrogenase-dependent acetylene reduction, and nodule soluble protein were studied during vegetative regrowth of detopped birdsfoot trefoil (Lotus corniculatus L.) seedlings grown in the glasshouse. Nodules senesced rapidly for a period of 14 days following shoot removal, but then pink nodule populations increased as shoot regrowth occurred. The structural sequence of senescence was similar in nodules whether the result of either aging or shoot removal.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 0 publications
4
23
0
2
Order By: Relevance
“…More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21). In S. rostrata, these factors elicit the division of cortical cells at the axils of lateral roots (21) (16) and Lotus corniculatus (40). Infection droplets containing several bacteria have also been noted for Vigna radiata (25).…”
Section: Discussionsupporting
confidence: 54%
“…More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21). In S. rostrata, these factors elicit the division of cortical cells at the axils of lateral roots (21) (16) and Lotus corniculatus (40). Infection droplets containing several bacteria have also been noted for Vigna radiata (25).…”
Section: Discussionsupporting
confidence: 54%
“…One route for infection occurs in lateral roots of both flooded and non-flooded L. uliginosus, which were infected via root hairs. This is the most commonly observed infection process in typical indeterminate and determinate temperate and\or crop legumes , where newly-formed root hairs are the most infectible sites (Hirsch, 1992), and has been reported previously with non-flooded L. corniculatus and L. japonicus (Ranga Rao, 1977 ;Vance et al, 1982 ;Szczyglowski et al, 1998).…”
Section: Infection Of Flooded and Non-flooded Roots And Stemssupporting
confidence: 59%
“…In these nodules, infection threads were much smaller and relatively scarce ( Fig. 4c) compared with earlier stages and, as with L. corniculatus and L. japonicus (Vance et al, 1982 ;Szczyglowski et al, 1998), further development of the infected tissue was by division and expansion of already infected cells, rather than by new infections. In contrast to MAC236, MAC265 labelled infection threads and infection droplets relatively lightly (compare the silver-enhanced sections in Fig.…”
Section: Germination and Nodule Development Under Floodingmentioning
confidence: 87%
See 2 more Smart Citations